Ecumenical Reflection on theEucharist as Sacrament of ChristianLove: Implications for ChurchIdentity and Vocation (Theological Kronos, 2024)
This paper seeks to contribute to ecumenical discussions on thesacrament of Eucharist from a pneumatological approach. Startingfrom the theology of John Wesley and Thomas Aquinas, the authorargues that Communion is a sacrament that communicates divine lovethrough the Incarnate Christ by the power of the Spirit. As a result, theEucharist shapes the identity and vocation of the church as the Bodyof Christ in the world. Further, in Communion, the Spirit leads thelocal Christian assemblies - as localized Bodies of Christ - toward acatholicism of encounter and inclusion rather than fragmentation andcompetition. The paper concludes that the Lord’s Table nourished aspirituality that seeks to embody Christ’s love for the suffering andmarginalized neighbor. The author invites further reflection on theEucharist as a liturgical practice that, rather than dividing, motivatesecumenical work.
Keywords: Eucharist; Communion; Lord’s Table; Medicine of Immortality; Pneumatology; Ecumenism; Catholicism; Body of Christ; Love